Vitamins in Prevention and Treatment of Allergic Diseases in Children - S. G. Makarova; L. S. Namazova-Baranova (Union of pediatricians of Russia, 2015)
It is known that a child cannot receive the sufficient amount of all vitamins and minerals with the regular contemporary ("Western") type of diet. The issue of vitamin deficiency is characteristic of a considerable part of population of Russia, including children. Vitamin deficiency is even worse in children with allergic pathologies than in similar age groups. As use of vitamin/mineral complexes in children with allergic diseases raises specific concerns among physicians and parents due to possible adverse reactions, discussion of the need and safety of vitamin prevention and vitamin therapy in this category of patients was chosen as the topic of this review. The article presents the contemporary data on the role of vitamins in a child's immune response formation, as well as in the pathogenesis of allergic diseases. The authors recount new data on numerous biological effects of vitamin D, including the immune system level, in detail. The review of clinical studies of use of vitamin/mineral complexes in children with allergies involved both foreign and Russian studies, including the considerable clinical experience accumulated right at the Scientific Center of Children's Health. It has been shown that use of vitamins both for preventive purposes and for treatment of allergic diseases in children is reasonable not only because it reliably affects immune response, but also due to a deficiency of a range of vitamins in immunopathogenesis of an allergological pathology.